Students’ engagement in school: analysis according to self-concept and grade level - Veiga, Feliciano Henriques (2014)
This article is a product of the project PTDC/CPE-CED/114362/2009 - Envolvimento dos Alunos na escola: Diferenciação e Promoção/Students Engagment in School: Differentiation and Promotion, financed by National funding, through the Fundação para a Ciência e Tecnologia (FCT).